A Generalization of the Shortest Path Problem to Graphs with Multiple Edge-Cost Estimates (Student Abstract) - Weiss, Eyal (Proceedings of the International Symposium on Combinatorial Search, 2023)
The shortest path problem in graphs is a cornerstone of AI theory and applications. Existing algorithms generally ignore edge weight computation time. In this paper we present a generalized framework for weighted directed graphs, where edge weight can be computed (estimated) multiple times, at increasing accuracy and run-time expense. This raises a generalized shortest path problem that optimizes different aspects of path cost and its uncertainty. We describe in high-level a complete anytime algorithm for the generalized problem and discuss possible future extensions.